Investigating textile wastewater treatment by electro-Fenton method with Fe-MIL-88(A) catalyst composited with graphene oxide - Farzane Esmaili; Hasti Hasheminejad; Kimia Zarean Mousaabadi (Water Resources and Industry)
The textile sector is one of the most complex industries that has significant problems due to the high toxicity and non-biodegradable properties of its dyes. Pollutants in this industry are a threat to living organisms and the environment, so their purification is of great importance. Recently, advanced oxidation processes (AOPs) have been more effective than other methods of treating this wastewater. Therefore, the focus of this study is on the synthesis of MIL-88A(Fe)/rGO for the removal of organic substances from textile wastewater using the electro-Fenton method.MIL-88(A) nanorods were first synthesized by hydrothermal method and embedded in graphene oxide (GO) substrate. Then, the synthesized composite was examined through spectroscopic and microscopic techniques, all analyses showed the correct formation of MIL-88A(Fe)/rGO structure. In each experiment, the value of the current density and the distance of the electrodes were considered equal to 9 Am−2 and 1 cm, respectively. The response surface method (RSM) was utilized to optimize parameters such as pH, time, the quantity of MIL-88A(Fe)/rGO composite, and the concentration of Na2S2O8 oxidant. The optimal conditions for conducting the test are pH 5, duration of 60 minutes, MIL-88A(Fe)/rGO composite concentration of 0.61 g/L, and oxidizer concentration of 0.017 M. According to the obtained optimal values, COD removal efficiency from textile factory wastewater is statistically and experimentally equal to 76.5 % and 78 %, respectively. The results of the electro-Fenton process demonstrated the promising efficiency of the MIL-88A(Fe)/rGO composite with environmentally friendly titanium and graphite electrodes, surpassing previous studies in accelerating the purification process.